Image Encryption using Simple Algorithm on FPGA - Barlian Henryranu Prasetio; Eko Setiawan; Adharul Muttaqin (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
Data security becomes one of the things that need to be considered. The Sum of Product (SOP) Encryption is one of simple algorithm. The SOP encryption is not a public-key system to encrypt data. it is almost unbreakable through brute force method and vulnerable to attack because the encryption models have a fixed pattern. However, this drawback can be avoided through the compression process to remove the pattern file. SOP encryption algorithm can use a Boolean algebra combination functions such as AND gate and OR gate. Simple algorithm in hardware language VHSIC Hardware Description Language (VHDL) is on data bits level. The purpose of this research is implementation of image encryption algorithm to produce a quick image encryption system. From result test, the image processing time without encryption average 4.999ns/px and 13.51ns/px with encryption.